H HUBUNGAN KARAKTERISTIK TERHADAP PENGETAHUAN MITIGASI BENCANA BANJIR DI DESA X - Muthmainnah, Muthmainnah (Journal of Nursing Invention, 2023)
Background: Flood disasters often occur in several regions in Indonesia, especially in southern Kalimantan in the village X area. this is often a flood disaster in the area. The government's efforts in making residents aware are by means of socialization through approaches and guidance to all residents about flood disaster mitigation in dealing with flood disasters in Village X. In mitigation knowledge, of course, education is very interrelated, as well as the age of mitigation knowledge, of course, it will be easy to understand at the age of 20 years and above. Objective: To analyze the relationship between characteristics and flood disaster mitigation knowledge in X village. Methods: This study uses correlation with cross-sectional research design, quantitative approach. conducted in village X Banjar district. The population amounted to 612, the sample amounted to 86 people, the sampling technique used purposive random sampling. The research instrument used was a questionnaire with a total of 15 questions. The results of the statistical analysis test can be interpreted with the formulation of the hypothesis. If the price p> α (0.05), then Ho is accepted so that it can be interpreted that there is no relationship. Results: The results of the analysis test on age showed that the p value showed more than 0.05 (0.684) sig. (p-value) Age obtained from the Spearman test results is> 0.05. The results of the analysis test on education show that the p value shows more than 0.05 (0.488) The sig. (p-value) Education obtained from the Spearman test results is> 0.05. Which means H0 is accepted, that is, there is no relationship between characteristics (age and education) on flood disaster mitigation knowledge in village x. Conclusion: there is no relationship between characteristics and mitigation knowledge.